Do Olivine Crystallization Temperatures Faithfully Record Mantle Temperature Variability?. (22nd April 2021) - Matthews, Simon; Wong, Kevin; Shorttle, Oliver; Edmonds, Marie; Maclennan, John
Abstract: Crystallization temperatures of primitive olivine crystals have been widely used as both a proxy for, or an intermediate step in calculating, mantle temperatures. The olivine‐spinel aluminum‐exchange thermometer has been applied to samples from mid‐ocean ridges and large igneous provinces, yielding considerable variability in olivine crystallization temperatures. We supplement the existing data with new crystallization temperature estimates for Hawaii, between 1282 ± 21 and 1375 ± 19°C. Magmatic temperatures may be linked to mantle temperatures if the thermal changes during melting can be quantified. The magnitude of this temperature change depends on melt fraction, itself controlled by mantle temperature, mantle composition and lithosphere thickness. Both mantle composition and lithosphere thickness vary spatially and temporally, with systematic differences between mid‐ocean ridges, ocean islands and large igneous provinces. For crystallization temperatures to provide robust evidence of mantle temperature variability, the controls of lithosphere thickness and mantle lithology on crystallization temperature must be isolated. We develop a multi‐lithology melting model for predicting crystallization temperatures of magmas in both intra‐plate volcanic provinces and mid‐ocean ridges. We find that the high crystallization temperatures seen at mantle plume localities do require high mantle temperatures. In the absence of further constraints on mantle lithology or melt productivity, we cannot robustly infer variable plume temperatures between ocean‐islands and large igneous provinces from crystallization temperatures alone; for example, the extremely high crystallization temperatures obtained for the Tortugal Phanerozoic komatiite could derive from mantle of comparable temperature to modern‐day Hawaii. This work demonstrates the limit of petrological thermometers when other geodynamic parameters are poorly known. Plain Language Summary: The temperature inside the Earth varies a lot. There are many ways of measuring the mantle's temperature in the present‐day, but to understand how our planet has changed through time, we need to know how hot its interior was in the past. One of the ways we can estimate mantle temperatures from ancient and modern rocks is from their crystal chemistry. By measuring the aluminum content in crystals of olivine, we can estimate their crystallization temperature. We do this for crystals from Hawaii. To turn the crystallization temperatures into the mantle temperature we need to know the proportions of minerals the mantle is made of. However, we often don't know all of this information. Using a new model of mantle melting we can calculate how uncertain the mantle temperature is when we only have a crystallization temperature. We find that the mantle under Hawaii is 1582 ± 65°C, much hotter than normal mantle, which has a temperature 1364 ± 23°C. We also apply our method to crystallization temperatures from other locations, including ancient volcanic rocks. We find that crystallization temperatures from large igneous provinces, formed by unusually hot mantle, are consistent with their mantle having a similar temperature to Hawaii Key Points: Hawaiian olivines crystallize at hotter temperatures than olivines in MORB Models are developed to link crystallization temperature to mantle temperature Mantle plumes may have had a similar distribution of temperatures throughout the Phanerozoic